The role of the BRICS countries in supporting foreign direct investment for third world countries subject to Western economic sanctions (An analytical study of the Syrian Arab Republic 2000-2022) - ناصر الدين زينا; محمد معن ديوب; دريد العيسى (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed at the following: Determine the degree of contribution of the BRICS countries to foreign direct investment in Syria in light of Western sanctions between the years 2000-2011. And determining the degree of contribution of the BRICS countries to foreign direct investment in Syria in light of Western sanctions between 2012-2022. And a statement of the ability and potential of the BRICS countries in the face of Western sanctions imposed on allied developing countries. The descriptive analytical method was used in the study. The study also reached a set of results, the most important of which are the following: There is no effective role for the BRICS countries in supporting foreign direct investment to Syria in light of the economic sanctions imposed by America and countries between the years 2000-2011. There is no effective role for the BRICS countries in supporting foreign direct investment in Syria in light of the economic sanctions imposed by America and countries between 2012-2022. The current war and economic sanctions have affected foreign direct investment in Syria significantly between 2012-2022. The economic sanctions imposed on Syria did not affect the attraction of foreign direct investment from various countries of the world, including America, between the years 2000-2011.